A theoretical framework for interaction of nursing discipline with genetics and genomics - Jiale Hu; Leilei Yu; Shokoufeh Modanloo; Yiyan Zhou; Yan Yang (Elsevier, 2018)
Background: Since the completion of the Human Genome Project, health science has been strongly influenced by the advances in genetics and genomics. However, the progress of embracing genetics and genomics into nursing discipline is limited. One of the main barriers is lack of understanding on the relevancy of genetics and genomics to nursing discipline. Objectives: This paper aims to synthesize and develop a theoretical framework for the interaction of nursing discipline with genetics and genomics. Methods: Through content analysis and constant comparative method, a theoretical framework was developed from synthesis of the studies regarding nursing and genetics/genomics indexed in multiple English and Chinese databases. Results: Four main theoretical statements were constructed in the framework: 1) There are three ways to show how genetics and genomics can influence nursing discipline: a new specialty, new technologies and a new lens; 2) The significant contribution of nursing discipline to genetics and genomics lies in how nurses could focus on the association between human responses and genes and how nurses could advocate for their clients in the genetic and genomic era; 3) A paradigm shift occurs after a constant interaction of nursing discipline with genetics and genomics; 4) Implementation strategies could be used to facilitate the integration of genetics and genomics to nursing discipline and advance the paradigm shift. Conclusions: The framework will help to understand the relationship between nursing discipline and genetics and genomics and implicate the future studies integrating genetics and genomic science into nursing discipline. Keywords: Advanced nursing practice, Genetics and genomics, Theoretical frameworks